Thermo-physical and mechanical characterization of cement-based mortar incorporating spent tea. (15th July 2022) - Horma, Othmane; Charai, Mouatassim; El Hassani, Sara; El Hammouti, Aboubakr; Mezrhab, Ahmed
Abstract: The use of biomass waste and plant fibers as aggregates for traditional binders has proven to be a green promising solution for reducing the overall energy consumption and carbon dioxide emissions related to the construction sector. Most research on plant-based additives reported an improvement in thermal insulation at the expense of mechanical strength. Thus, balancing the thermo-mechanical properties is a key to produce innovative insulating materials. In this work, the potential use of Spent Tea (ST) in the manufacturing of bio-sourced cement-based mortars was studied. Different weight ratios ranging of 0–10% were used to evaluate the influence of ST content on the cement performance. Thermal, mechanical, and physical properties of the produced bio-composites were characterized. The results showed that increasing ST content leads to a significant decrease in thermal conductivity (67%), thermal diffusivity (57%), density (24%), and compressive strength (97%). At last, it was found that adding up to 2.5 wt% ST meets the structural requirements of lightweight concretes (>3.5 MPa) and could be used for wall structures. However, the composite incorporating 7.5 wt% of ST should exclusively serve for insulation purposes. Highlights: Development of green cement-based mortar incorporating spent tea ST. Investigation of the mineralogical and chemical properties of cement and ST. Experimental measurement of thermo-mechanical and physical properties. Determining the ST/cement (STC) composites suitable for structural and insulating use. Deducing the optimal ranges of ST content additions with regards to potential engineering applications.